Upaya Kepala Sekolah Mengatasi Permasalahan Kualitas Akhlak di Zaman Modern Berbasis Islam Pada Peserta Didik di MTs Negeri 4 Karawang - Anisa Aurelia Putri; N. Fathurrohman (Peneliti.net, 2022)
Writing this paper aims to determine the efforts of school principals to overcome the problem of moral quality in modern times with Islam-based students in MTS Negeri 4 Karawang. This writing conducts research obtained by means of documents, literature studies and other data collection techniques. As for the background of this writing because students or students must have good moral qualities, as well as for the current school principal must be concerned with the development of moral (moral) as well. Because, moral values ​​are very important to ensure honesty, discipline, fairness, order, security and harmony in social relations between the school environment and outside the school (community). What does it mean if someone has intellectual intelligence but has bad morals. The method used, namely data collection, and data analysis. The results showed that, the most effective way for school principals to instill good morals in students lies in the character education model that exemplifies, especially the good attitude so that the quality of morals in MTS Negeri 4 Karawang has good morals